CONSTITUTIONAL COURT OF THE REPUBLIC OF INDONESIA: SAFEGUARDING CITIZENS' CONSTITUTIONAL RIGHTS IN THE MIDDLE OF A PANDEMIC (International Seminar on Syariah and Law (INSLA), 2020)
Since the coronavirus's announcementthat COVID-19 is a pandemic, there are concerns that this coronavirus pandemic will hurtall human life sectors. The health and economic sectors are the most vital, causing many countries worldwideto experience outbreaks,andit is difficult to avoid them. Many countries are not ready to face this pandemic, resultingin more casualties and an economic recession. However, amid the outbreak, it turns out that there is still a country that can survive,and one of the factors that cause this country to survive is law enforcement.The process is carried out optimally and is supported by law enforcement officials who are also professional, independent and with integrity. In this study, the author will discuss the extent to which the Indonesian Constitutional Court's roleas the guardian of the constitution in safeguarding the constitutional rights of Indonesian citizens and providing legal certainty amid a pandemic.